PENINGKATAN KEMAMPUAN OPERASI PENJUMLAHAN MELALUI MEDIA BLOKJES PADA SISWA TUNANETRA KELAS II DI SLB NEGERI GOWA - Setiawan, Perlin; Kasmawati, Kasmawati; Syamsuddin, Syamsuddin (-, 2025)
This research examines the ability of addition operations in a blind student at SLB Negeri 1 Gowa. The aim of this research is to find out: 1) A description of the ability of addition operations in class II students at SLB Negeri 1 Gowa before implementing the blockjes media, 2) A description of the ability of addition operations in class II students at SLB Negeri 1 Gowa when implementing the blockjes media, 3 ) Description of the ability of addition operations in class II students at SLB Negeri 1 Gowa after implementing the blockjes media. The data collection technique is a written test. The research subject was a blind child with the initials MI. This research uses a quantitative approach with descriptive research type. The results of this research can be concluded: 1) A description of the ability of addition operations in class II students at SLB Negeri 1 Gowa before implementing the blockjes media was in the very low category, 2) A description of the ability of addition operations in class II students at SLB Negeri 1 Gowa after implementing Blokjes media is in the very high category, 3) There is an increase in the ability of addition operations in a class II blind student at SLBN 1 Gowa by applying the Blokjes media from a very low category to a very high category. Keywords: Blokjes Media, Addition Operation, Visually Impaired..